Pengaruh Edukasi Kesehatan Berbasis Video Animasi Terhadap Peningkatan Pengetahuan Kontrol Diri Seksualitas Komprehensif Pada Remaja - Lili Suryani (Nan Tongga Health And Nursing, 2026)
Teenagers in Indonesia generally start dating for the first time during their teenage years. As many as 33.3% of teenage girls enter into their first relationship between the ages of 15-17, while 34.5% of teenage boys begin dating before reaching the age of 15. Dating activities among teenagers aged 15-24 include holding hands (64% of girls and 75% of boys), kissing on the lips (30% of girls and 50% of boys), and petting (17% of girls and 33% of boys) (BKKBN in Lestari W, 2025). This study aims to determine the effect of health education using animated videos on knowledge about comprehensive sexual self-control in adolescents. This study is a quantitative study with a Quasy-Experimental design with a One Group Pretest-Posttest design approach. The sampling technique used the Total Sampling technique. The population in this study were all students of SMAN 13 Kerinci in 2025, totaling 80 people with a sample of 80 people. This data collection was carried out at SMAN 13 Kerinci, in June-August 2025. Data were analyzed using the Wicoxon test. Based on the results, the average knowledge of comprehensive sexual self-control in adolescents before being given health education was 9.98, while after being given health education the average was 13.98. There is an effect of health education using animated videos on knowledge about comprehensive sexual self-control in adolescents. It is hoped that schools will provide health education regarding comprehensive self-control and sexuality in adolescents through animated video media to increase knowledge related to healthy sexual behavior, so as to prevent unplanned pregnancies that have the potential to cause school dropouts.